Public transport reorganization through rational territory management - Estrada Cortez, Jorge Armando (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
In Mexico, the Concessioned Public Collective Transit (CPCT) arose as an alternative to compensate for the need for urban transportation in the 20th century. Through concessions, the government was able to delegate the exploitation of the public transit service to private associations. However, the lack of regulation has motivated the accelerated growth of the fleets as an attempt to cover the largest number of destinations. This service oversupply is traduced in a high redundancy of routes, increasing the vehicular density and inhibiting urban mobility. A special case takes place in the city of Morelia, Michoacan, where on a segment of an arterial road coexist 36 routes, which means up to 374 CPCT vehicles per km/h. In this work, it is proposed a methodology to identify the trajectories that allow unifying the most routes for a CPCT re-organization intended to reduce vehicular density and improve mobility. The trajectories were identified by constructing the maximum spanning tree (MST) of the graph of the current distribution of routes. Based on the MST, a CPCT re-organization scheme was proposed, consisting of three systems: backbone, feeder and local. The backbone system traverses the city from east to west, connecting the three main travel attractor/generator centroids. The feeder system is composed of nine routes, intended to allow the trips from the secondary centroids to the backbone. Finally, the local subsystem is intended to facilitate the trips from the inner of different bedroom cities and industrial complexes to the other two systems.

En México, el Transporte Público Colectivo Concesionado (TPCC) surgió como una alternativa para compensar las necesidades de transporte urbano del siglo XX. A través de los concesionarios, el gobierno pudo delegar la explotación del servicio de transporte público a asociaciones privadas. Sin embargo, la falta de regulación ha motivado el crecimiento acelerado de las flotillas, bajo el precepto de cubrir el mayor número de destinos. Esta sobre-oferta del servicio se traduce en una alta redundancia de rutas, incrementando la densidad vehicular y obstaculizando la movilidad urbana. Un caso especial tiene lugar en la ciudad de Morelia, Michoacán, en donde en un segmento de una vialidad arterial coexisten 36 rutas, lo que induce hasta 374 vehículos de TPCC por km/h. En este trabajo se propone una metodología para identificar las trayectorias que permitan unificar la mayor cantidad de rutas; para lograr una reo-organización del TPCC orientada a disminuir la redundancia y mejorar la movilidad. Las trayectorias se identificaron mediante la construcción del árbol de expansión mínimo (AEM) del grafo de distribución de rutas actual. Basándose en el AEM, se planteó un esquema de re-organización del TPCC compuesto por tres sistemas: troncal, alimentador y local. El sistema troncal atraviesa la ciudad de oriente a poniente, conectando los tres principales centroides atractores y generadores de viajes. El sistema alimentador se compone de nueve rutas, diseñadas para permitir los traslados desde los centroides secundarios hacia el sistema troncal. Por último, el subsistema local, está orientado a facilitar el traslado desde el interior de diferentes ciudades dormitorio y complejos industriales, hacia los otros dos sistemas.
Facultad de Ingeniería Civil. Maestría en Infraestructura del Transporte en la Rama de las Vías Terrestres
Keywords: info:eu-repo/classification/cti/7; FIC-M-2019-1889; Transporte público; Optimización de rutas; Simulación microscópica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3151